Evaluation of Some Blood Parameters in Anemic Patients in Relation to Periodontal Condition - Noor Sabah Irhayyim (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Periodontal diseases are the inflammatory process result from microbial-host interaction in the tissues surrounding the teeth. Gingivitis and periodontitis are the most common type of periodontal diseases. Anemia of the chronic disease(ACD) is common health problem occur in patients with acute or chronic activation of immune system and production of inflammatory cytokines, so it is resemble to periodontal diseases from this aspect.Aims of the study: To compare the clinical periodontal parameters (plaque index(PLI), gingival index(GI), bleeding on probing(BOP), probing pocket depth(PPD) and clinical attachment level(CAL)) and the levels of hemoglobin(Hb), mean cell volume(MCV), and Mean corpuscular hemoglobin(MCH) in blood, and correlate them in patients with gingivitis, chronic periodontitis(CP) and clinically healthy periodontium.Materials and method: 90 subjects included in the study with age range from 30-50 years old. There were divided into three groups: 30 patients with chronic periodontitis, 30 patients with gingivitis, and 30 subjects with clinically healthy periodontium. Blood samples were collected from the subjects for automated blood analyzer to determine the levels of Hb, MCV, and MCH, after clinical periodontal examination was done for(PLI,GI,BOP,PPD, CAL).Results: statistically highly significant differences among the groups (Gingivitis and chronic periodontitis) in PLI, GI and BOP score1. The highest mean value of Hb shown in control group(15.33) while the highest mean value of MCV demonstrated in gingivitis group(87.44) and the highest mean value of MCH demonstrated in control group(32.09). The correlation of Hb, MCV, and MCH with clinical periodontal parameter shown almost weak negative correlation.Conclusion: the periodontal diseases like other inflammatory diseases can lead to development of anemia type(anemia of chronic disease)and the severity of disease increase with increase the severity of periodontal diseases.